Mendiante et orgueilleuse ? L’université d’al-Azhar et l’enseignement supérieur égyptien (1860-1930) - Thomas Raineau (Revue des Mondes Musulmans et de la Méditerranée)
For a large part of the xixth century, the mosque and university of al-Azhar, the torchbearer of Sunni religious science in Egypt, kept a prevalent role in the instruction of the Egyptian elite. With the creation of the Superior Schools inspired by European models, and with their gradual expansion, al-Azhar started to be threatened as a major actor in the embryonic Egyptian Academia around 1900. Since al-Azhar was unable to fulfil the aspiration of an increasing part of the society for “modern” disciplines and methods, its graduates were confronted to a rising competition with those of institutions such as Dâr al-‘Ulûm or the School of the Cadis, for obtaining jobs of teachers or magistrates. The Great Mosque tried to respond to the threat by launching a radical reform of the studies that was hardly implemented in reality, and did not prevent al-Azhar to be slowly marginalized within Egypt’s higher education system at the dawn of the 1930s.